Metacomposite with auxetic and in situ sign reversible thermal expansivity upon temperature fluctuation. (June 2020) - Lim, Teik-Cheng
Abstract: This paper proposes a metacomposite that shrinks regardless of temperature decrease or increase, i.e. it exhibits positive and negative thermal expansions with cooling and heating, respectively, which leads to auxetic behavior. This metacomposite is constructed from rigid rods and bimaterial strips; the ends of the rigid rods are connected in series by freely-rotating pin joints while neighboring chains of rigid rods are linked by bimaterial strips that are connected to the mid-spans of the rigid rods by fixed joints. Thermal deformation results indicate that the magnitude of the coefficient of thermal expansion (CTE) of the metacomposite parallel to the rigid rod is about 3 times greater than that parallel to the bimaterial strips. Upon thermal deformation, prescription of stretching parallel to the chains of rigid rods indicate a Poisson's ratio that is approximately −1/3. Results also show that the effective in-plane CTE and Poisson's ratio are influenced by the CTE ratio of the bimaterial phases and aspect ratio of the bimaterial strip. The possibility of this auxetic metacomposite to achieve in situ sign-switching of CTE avails greater design options to the materials engineer. Highlights: A metacomposite is designed using bimaterial strips and rigid rods to give counter-intuitive properties. The Poisson's ratio is about −1/3. The metamaterial possesses both positive and negative thermal expansion in situ . The metamaterial exhibits negative thermal expansion upon heating but turns conventional upon cooling. Therefore, this metamaterial always shrinks whether temperature increases or decreases.